The origin of the A/G single nucleotide polymorphism of starch synthase IIa in rice and its relation to gelatinization temperature. Issue 2 (6th July 2021) - Song, Jiling; Hu, Yaqi; Deng, Guofu; Dai, Gaoxing; Bao, Jinsong
Abstract: Background and objectives: The domestication of cultivated rice ( Oryza sativa L.) has long been studied, and many agronomically relevant genes have undergone artificial selection. Among them, the selection history of the starch synthase IIa ( SSIIa ) has not been fully discovered. The SSIIa is a genetic factor that controls the gelatinization temperature (GT) of rice starch, an important parameter for rice cooking quality. Findings: The A/GC haplotype in SSIIa only presented in the japonica subspecies. GT was found to be strongly associated with SNPs in SSIIa, that is, G/GC haplotype rice had high or intermediate GT, while G/TT or A/GC haplotype rice had low GT. The nucleotide diversity (π) in japonica was much lower than that of indica and wild rice, indicating that a population bottleneck was experienced during japonica rice domestication. A possible positive selection on the A SNP of SSIIa in temperate japonica rice favoring low GT starch synthesis was proposed. Conclusions: The evolution of SSIIa in the japonica rice was possibly under positive selection favoring low GT rice, which requires low energy input for cooking. The A SNP of SSIIa is only present in the japonica rice, which might be derived from a recent mutation. There are two ways, A/GC and G/TT, to make japonica rice with low GT, explaining why all the temperate japonica rice cultivars have low GT. Significance and novelty: Findings of this study provide an understanding of why all the temperate japonica rice have low GT starch, because there are two ways to make it GT low.